First Report of the Signal Fly, Scholastes sp. (Diptera: Platystomatidae) Visiting Animal Carcasses in Malaysia - Dhang, C.C.; Chin, H.C.; McAlpine, D.; Kurahashi, H.; Ahmad, N.W.; Marwi, M.A.; Jeffery, J.; Lim, L.H.; Omar, B.; Sofian-Azirun, Mohd (Malaysian Society of Parasitology and Tropical Medicine, 2008)
Signal fly, Scholastes sp. (Diptera: Platystomatidae) was observed associated with animal carcasses in Malaysia. The first observation was on a monkey carcass, which was killed by using a handgun and immediately placed in a forested area in Gombak, Selangor while the second observation was on a pig that died of natural causes and whose carcass was placed in an oil palm plantation in Tanjung Sepat, Selangor. Both animal carcasses were visited by Scholastes sp. flies during the fresh decomposition period. However, the role Scholastes flies in the decomposition process remains unknown. In this paper, we report the occurrence of Scholastes sp. on animal carcasses in Malaysia for the first time.